Origin of Interrelation between Morality and Religious Views - Liubarskienė, Zita (Problemos, 1983)
The article is a study of the conceptions of the genesis of morality, religion and their interrelation in the primitive society that were formulated in the works on philosophy of the Republic. The conclusion is drawn that the most acceptable, both from scientific and ideological standpoint, are those views in accordance with which the rudiments of interrelation between morality and religious views can already be found in the primitive society – in the syncretic form of the development of the above social phenomena.